Metaphor and Ideology in the Business Press: The Case of the Endesa Takeover - Isabel Negro Alousque (Miscelánea: A Journal of English and American Studies, 2012)
Ideology is present in language (Fairclough 1989) and is embodied in a range of linguistic devices. Metaphor is one of such devices, as has been shown in recent research (Fairclough 1992; Dirven and Frank 2001). In this article we explore the metaphorical base of the Spanish and British journalistic discourse on a specific business issue —the Endesa takeover— and the way ideology operates. The empirical data for our survey have been drawn from two newspapers (El País, Financial Times) published over a period running from September 2005 to April 2007. Our main assumption is that metaphor has an ideological value which is manifested through the positive or negative axiologisation of the takeover.